VD_FINDINFO Jug / 2023 / 123 vom 5. Juli 2022 - VD Tribunal cantonal (2022)
CALOMNIE, DIFFAMATION, PREUVE LIBÉRATOIRE, INDEMNITÉEN GÉNÉRAL, PARTIE CIVILE, PLAIGNANT | 173 ch. 1 CP, 174 CP, 427 al. 2 CPP (CH), 432 al. 2 CPP (CH)